Cuidado e formação humanizadora na área da saúde humana : uma perspectiva a partir da teoria das emoções de Martha Nussbaum - Deggerone, Rosmarí (2022)
This present thesis aims to defend a perspective of a humanizing formation in the health area - especially the nursing - based in the Martha Nussbaum's Theory of Emotions, that present itself as a fundamental theorical contribuition to set a contrapoint to the competences and abilities listed in the National Guidelines, in the Pedagogical Progects and in the Teaching Plans in the nursing area and its limitation in the face of the complexity that human being in the daily care. The research problem is guided by the following question: What is the scope of a concept of compassionate and empathic care as unveiling of the human to think in a humanizing formation in the human health area? The study presents as its main hypothesis that Nussbaum, through his Emotions Theory, enable to explein a compassionate care conception as an unveiling of the human. This enables to thematize the relashionship between the human condition, emotions and humanizing formation in the human health area. The present study methodology is a bibliographical theoretical nature and adopts a reconstructive-hermeneutics methodological approach to the Martha Nussbaum's concepts and the other secondary studiend authors studiend. The thesis is organized on four chapters: initially approaches the Nussbaum`s human condition concept. Then, it thematizes the emotions and the human condition, as well as its link with the human concealment problem. In the third part, it presents a compassionate and empathic care conception as a “human unveiling” through the link established between the “profitable” emotions and the humanizing formation in the health area. in the fourth chapter, advances thematizing the relationship between care and education, defending a extended and compassionate concept of care based in the Nussbaum's Emotions Theory. It is concluded that the Nussbaum's Emotions Theory can be linked to the health area as important possibility to contemplate the formation and health education, according to the specific competences and abilities of the area, but associating these with a more compassionate and empathic bias. Therefore, the expanded conception of care based on the compassion and on empathy proposed would make it possible to go beyond the reductionism present in many institutional practices in health na in the curricular bases in force in the courses that form the professionals.